ANALISIS NILAI WILLINGNESS TO PAY PER QUALITY ADJUSTED LIFE YEAR TERAPI PENYAKIT MODERATE MASYARAKAT DI KOTA BANJARMASIN TAHUN 2019 - Melviani; Setia Budi (BORNEO JOURNAL OF PHARMASCIENTECH, 2020)
Health services in Indonesia have not been maximized to cover the needs of patients who have moderate disease. Furthermore, Pharmacoeconomics approach is most recommended for cost and quality control namely Cost utility analysis. The interpretation of the cost-effectiveness ratio requires a cost-effectiveness threshold to determine whether a health technology is cost-effective or not. One approach that can be used is by finding the estimation of willingness to pay per quality adjusted life years. The research objective was to determine the estimation of willingness to pay per quality adjusted life year for the moderate disease community in Banjarmasin and to find out the factors that influence it. The research method used a cross-sectional approach. The survey was conducted tothe community in Banjarmasin in 2019 by using stated preference methods with the contingent valuation approach. The samplewas 100 respondents. The research instrument was questionnaire which was consisted of measuring the value of WTP using the dichotomous bidding game method, the measurement of utility used EQ-5D based on a hypothetical scenario of moderate disease utility value. Analysis used bivariate correlation analysis spearman. The findings showed that the average of WTP per QALY EQ-5D-5L was Rp. 19,538,910 and the analysis of the variable characteristics of the respondents to the WTP per QALY obtained R square 0.397 (p = 0.026), which means that 39% of the dependent variable together will affect WTP. per QALY. This research is expected to provide input on the CE-Threshold based on community preferences.